TINDAK PIDANA PEMBUNUHAN BERDASARKAN HUKUM ISLAM - Rahmad Alamsyah (Ensiklopedia of Journal, 2020)
The main problems in this study are: How are the criteria for a murder said accidentally and intentionally based on the perspective of Islamic law? What is the legal basis for the conviction of perpetrators of murder accidentally and intentionally based on the perspective of Islamic law? This type of research is normative legal research specifically discussing murder according to Islamic law. Benchmark /criteria for intentional killing is an act carried out by someone with the aim of killing another person by using a tool deemed appropriate to kill. Benchmark/accidental killing criteria (khata) is an act carried out by someone with no intentional element that causes another person to die. The legal basis for the deliberate and deliberate punishment of the perpetrators of murder based on the perspective of Islamic law is as follows: Actors of intentional murder, the victim's family can decide on one of three choices, namely (1) qishash, namely the punishment of retribution according to the suffering of the victim 2) Diat, namely the killer must pay a fine of 100 camels, or 200 cows or 1,000 goats, or other forms such as money worth the price. The diat is handed over to the victim's family, (3) the family forgives whether it must be on condition or unconditionally. The perpetrators of unintentional killings, the family is given a choice, namely (l) the perpetrator pays the payment; (2) paying for kifarah; (3) if they are not able, the perpetrators of the murder are given a moral sentence.